Analysis of roll wave characteristics under low liquid loading two‐phase flow conditions. Issue 7 (2nd February 2017) - Karami, Hamidreza; Pereyra, Eduardo; Sarica, Cem; Torres, Carlos F.
Abstract : An experimental study is conducted using a 0.152‐m ID facility to investigate the wave characteristics of two‐phase stratified wavy flow in horizontal pipelines. The experiments are conducted under low liquid loading condition, which is very commonly observed in wet gas pipelines. The experiments are conducted with water as the liquid phase, and repeated with 51 wt % of monoethylene glycol (MEG) in the aqueous phase to analyze the effects of MEG presence on wave characteristics. The experimental range of this study covers superficial gas velocity, vSg, values of 9–23 m/s and superficial liquid velocity, vSL, values of 0.01–0.02 m/s. Similar test matrices are completed for the cases with and without MEG in the aqueous phase. A conductivity probe system is used to measure the wave characteristics at the liquid–gas interface. These characteristics include the wave celerity, frequency, amplitude, length, and liquid film thickness. The experimental oil–air wave characteristics data of Gawas et al. (Int J Multiphase Flow. 2014;63:93–104) is also used for comparison purposes. The trends in the resulting wave characteristics with respect to input parameters are investigated, for oil, water, or MEG–water mixture as the liquid phase. Common predictive methods for interfacial wave celerity, including shallow water theory, Watson (Proceedings of the 4th International Conference in Multi‐Phase Flows, Nice, France. 1989:495–512), Paras et al. (Int J Multiphase Flow. 1994;20(5):939–956), Al‐Sarkhi et al. (AIChE J. 2012;58(4):1018–1029), and Gawas et al. (Int J Multiphase Flow. 2014;63:93–104) are evaluated in comparison with the experimental data. The results of the wave frequency correlation of Al‐Sarkhi et al. (AIChE J. 2012;58(4):1018–1029) are also compared with the experimental wave frequency data. Lastly, a correlation is developed to predict the relative wave amplitude, as a function of superficial gas Weber number and liquid velocity number. Most of the commonly used two‐phase stratified flow models are developed with the assumption of steady‐state conditions, and neglect the transient wave effects. This study provides valuable experimental results on wave characteristics of stratified wavy flow for different types of liquid phase. Moreover, a comprehensive analysis of the parameters affecting the wave characteristics of stratified wavy flow is presented. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3177–3186, 2017